“God or Idol?” Research exploration of AI idolization awareness in poster design - Andreas James Darmawan; Sugiyanto Sugiyanto; Putri Karin Cinthya; Sitinjak Eunike Yolanda Zefanya (Pascasarjana Institut Seni Indonesia Surakarta, 2026)
This study aims to explore how poster design can be utilized as a medium for critical reflection on the relationship between humans and artificial intelligence (AI). Using a research-through-design approach, the study developed and compared two poster concepts: a collaborative human–AI poster and a provocative AI-idolization poster. The design process began with the creation of a poster intended to convey a message about the respective positions of humans and AI. A knowledge-tree theme was selected to represent harmony between organic and technological elements. The poster depicts humans and AI sitting side by side beneath a tree with circuit-shaped roots, symbolizing synergy and connectedness. However, despite being aesthetically appealing and communicative, this visual model relies on a widely used metaphor, potentially resulting in a weak awareness effect because audiences are already accustomed to similar representations. As an alternative, a second approach was developed through a provocative poster that combines a religious figure with robotic elements to represent AI as a modern idol. This unconventional visual creates a sense of shock and prompts audiences to reconsider the position of AI, questioning whether it should be perceived as a collaborative partner or excessively glorified. Using a qualitative descriptive approach, the results indicate that the AI-goddess poster is more effective in stimulating critical awareness than the knowledge-tree poster. Through visual rhetoric and semiotic analysis, the findings suggest that unconventional visual metaphors have greater potential to stimulate critical reflection on the position of AI in contemporary society.